The implication of the economic crisis on the Filipino community in Iceland and why families in the Philippines are affected - Violeta Tolo Torres 1967- (2013)
The research question in this study is “ The implication of the economic crisis on the Filipino community and why families in the Philippines are affected”. When Iceland was badly hit with the financial crisis in 2008, it not only affected the Filipinos in Iceland but also their families in the Philippines. The purpose of this study is to determine the impact of this crisis to the Filipinos being in a country experiencing a financial crisis and its aim is to shed some light on why and how it affected their lives in Iceland and why it is affecting the lives of their families in the Philippines as well. This is a qualitative research and the methodology that guided this study is phenomenology. Purposeful sampling was used in selecting the participants. The sample consists of 14 participants, ten females and four males, including a short interview with the Filipino Honorary Consul in Iceland for a general overview of the Filipino community. The participants have been residing in Iceland for many years. They were chosen through snowball sampling technique where the initial participant suggest another possible participants and so on. Many names were suggested but the researcher had to choose from among them those who would most likely fit the research criteria and who would likely provide the answer to the research question. The essential criteria is that they have experienced the phenomenon and willing to participate and grant permission to tape record the interview for the purpose of this study. Using ten open-ended questions in the interview, the researcher was able to collect and transcribe the data, and then the analyses were clustered into themes. Five themes emerged that described the research. The first theme “ A chance to improve the family situation; financial hardship and family reunification” describes how the participants came to Iceland after an invitation to work from a member of the family or from a friend for the purpose of improving the life of their loved ones in the Philippines. The second theme “ ...